Nonlinear structural reorganisation of corn starch induced by high-pressure processing regulates its thermal, pasting and hydration behaviour - Wen-Chien Lu; Yung-Jia Chan; Ching-Jung Lin; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Long-term increases in urinary metals are associated with lipid peroxidative but not oxidative DNA damage in adolescents and young adults: A 10-year prospective cohort study - Chien-Yu Lin; Po-Chin Huang; Hui-Ling Lee; Ta-Chen Su (Environmental Pollution, 2026)

Synergistic transition binary metal oxide with multiwalled carbon nanotubes interfaces enabling sensitive electrochemical detection of preservative agent diphenylamine - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Rajalakshmi Sakthivel; Ting-Yu Liu; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Laminar nanofiltration composite membranes based on two-dimensional aluminum-tetrakis(4-carboxyphenyl)porphyrin (Al-TCPP) nanosheets for efficient dye/salt wastewater treatment - Shao-Ju Lu; Chun-Po Hu; Chien-Chieh Hu; Chia-Her Lin; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Journal of Environmental Chemical Engineering, 2026)

Statistical optimization of biochar production via high-temperature carbonization through Taguchi and principal component analysis approaches - Jamin Jamir Escalante; Wei-Hsin Chen; Chien-Yuan Su; Po-Han Li; Kun-Yi Andrew Lin; Kanit Manatura (Fuel, 2026)

Nitrosamines in Pharmaceuticals and the Environment: Genotoxic Impurities, Detection Strategies, and Developmental Health Risks - Uday Shashikumar; Hem Nikhilesh Naik; Jayashree E. Veerabhadra; Vimalkumar Krishnamoorthi; Pei-Chien Tsai; Po-Chin Huang; Yi-Hsun Chen; Smita Jauhari; Yuan-Chung Lin; Vinoth Kumar Ponnusamy; Gopalakrishnan Kumar (Current Pollution Reports, 2026)

Redox-active flower-like ZnMoO4 decorated on 2D graphene oxide nanohybrid as an efficient catalyst for sensitive electrochemical detection of a nitrofuran derivative in environmental and biological matrices - Amulya Garadi; Sanjay Ballur Prasanna; Po-Chun Chen; Gagankumar Sakleshpur Kumar; Nandini Nataraj; Yu-Chien Lin; Xinke Liu; Ting-Yu Liu; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Breaking the ‘forever’ bond: photocatalytic degradation of per- and polyfluoroalkyl substances using ternary photocatalysts - Uday Shashikumar; Himanshi Goel; Ishika Rana; Pei-Chien Tsai; Kiran B. Manjappa; Phuong V. Pham; Gangadhar Andaluri; Kumar Rakesh Ranjan; Yuan-Chung Lin; Vinoth Kumar Ponnusamy; Po-Chin Huang (Reviews in Environmental Science and Bio/Technology, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

Advances and Challenges of Tissue Vascular Scaffolds and Supercritical Carbon Dioxide Technology in Cardiovascular Diseases - Horng-Ta Tseng; Yi-Wen Lin; Shih-Ying Sung; Yi-Ting Tsai; Chen-Wei Liu; Po-Shun Hsu; Chien-Sung Tsai; Feng-Yen Lin (Tissue Engineering and Regenerative Medicine, 2025)

Impact of Coal-Fired Power Plants on Suspended Sediment Concentrations in Coastal Waters - Zhi-Cheng Huang; Po-Chien Lin; Po-Hsun Lin; Shun-Hsing Chuang (Journal of Marine Science and Engineering, 2025)
Many coastal coal-fired power plants utilize seawater flue gas desulfurization (SWFGD) systems, which may pose risks of heavy metal attachment on suspended sediments. Understanding variations in suspended sediment concentration (SSC) is therefore useful for controlling marine pollution. We studied two power plants as examples of discharging SSC using continuous measurement techniques. Monitoring sites at intake and discharge points and the surrounding coastal areas of the power plants was conducted across seasons. The first case study, Linkou Power Plant, is located in a high-SSC region influenced by monsoon winds and wave activity. Results indicate that SSC levels at all the monitoring sites are correlated with environmental factors of wind and wave conditions, with strong positive correlations observed between the intake and discharge points. In contrast, the Dalin Power Plant is located within an international harbor, where the SSC levels are generally low; however, sudden increases in SSC are observed at the intake point due to disturbances from vessel activities. These sudden increases are not evident at the discharge point, suggesting a sink of SSC may occur within the system. These results demonstrate that the two studied power plants have limited effects on the increase in SSC; the SSC in the discharge point is mainly related to the SSC input at the intake point. Effective management of SSC at the intake may help mitigate coastal pollution caused by SSC discharge and reduce the risk of harmful substances adhering to suspended solids in the discharging wastewater.

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Self-assembled mesoporous silica decorated with biogenic carbon dot nanospheres hybrid nanomaterial for efficient removal of aqueous Methoxy-DDT via a Short-Bed Adsorption column technique - Ajith Manayil Parambil; Eepsita Priyadarshini; Rohit Goutam; Pei-Chien Tsai; Po-Chin Huang; Paulraj Rajamani; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Research, 2024)

Advances in perfluoro-alkylated compounds (PFAS) detection in seafood and marine environments: A comprehensive review on analytical techniques and global regulations - Prasath Ramasamy Chandrasekaran; Jeganathan Chinnadurai; Yee Cheng Lim; Chiu-Wen Chen; Pei-Chien Tsai; Po-Chin Huang; Mohsen Gavahian; Gangadhar Andaluri; Cheng-Di Dong; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Carbon and graphene quantum dots based architectonics for efficient aqueous decontamination by adsorption chromatography technique - Current state and prospects - Ajith Manayil Parambil; Shijin Rajan; Po-Chin Huang; Uday Shashikumar; Pei-Chien Tsai; Paulraj Rajamani; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Research, 2024)

Demystifying the interconnections among natural resources, fintech, green technologies, and sustainable environment in E-7 nations - Hsiao-Hsien Lin; Chao-Chun Hsu; Po-Hsuan Wu; Chih-Chien Shen; Gan-Hong Chen (Resources Policy, 2024)

Rapid identification and monitoring of cooking oil fume-based toxic volatile organic aldehydes in lung tissue for predicting exposure level and cancer risks - Karthikeyan Prakasham; Swapnil Gurrani; Chia-Fang Wu; Ming-Tsang Wu; Tusty-Jiuan Hsieh; Chiung-Yu Peng; Po-Chin Huang; Anbarasu Krishnan; Pei-Chien Tsai; Yu-Chia Lin; Bongee Tsai; Yuan-Chung Lin; et al. (Chemosphere, 2023)

High carriage rate of extended‐spectrum β‐lactamase Enterobacterales and diarrheagenic Escherichia coli in healthy donor screening for fecal microbiota transplantation - Chien Chuang; Kuei-Chuan Lee; Yen-Po Wang; Pei-Chang Lee; Tien-En Chang; Yi-Hsiang Huang; Yi-Tsung Lin; Ming-Chih Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Simultaneous biomonitoring of volatile organic compounds’ metabolites in human urine samples using a novel in-syringe based fast urinary metabolites extraction (FaUMEx) technique coupled with UHPLC-MS/MS analysis - Swapnil Gurrani; Karthikeyan Prakasham; Po-Chin Huang; Ming-Tsang Wu; Chia-Fang Wu; Yu-Chia Lin; Bongee Tsai; Anbarasu Krishnan; Pei-Chien Tsai; Vinoth Kumar Ponnusamy (Chemosphere, 2023)

Free-standing vertically aligned tin disulfide nanosheets for ultrasensitive aptasensor design toward Alzheimer’s diagnosis applications - Bayu Tri Murti; Yi-June Huang; Athika Darumas Putri; Chuan-Pei Lee; Chien-Ming Hsieh; Shih-Min Wei; Meng-Lin Tsai; Chih-Wei Peng; Po-Kang Yang (Chemical Engineering Journal, 2023)

Promoting human rights for Taiwan’s fishermen: Collaboration with the primary source countries of Taiwan’s DWF migrant fishermen - Po-Chih Hung; Hsiao-Chien Lee; Chih-Cheng Lin; Wen-Hong Liu (Frontiers in Marine Science, 2022)
Taiwan is one of the largest distant water fishing (DWF) nations worldwide, and relies largely on the migrant labor to keep costs low. However, this industry has caused Taiwan to be listed in the 2020 “List of Goods Produced by Child Labor or Forced Labor” of the U.S. Department of Labor. In view of this, the Taiwanese government is actively adopting further management measures to supervise the domestic and foreign fishermen agencies. It is because the latter has been involved in many disputes, especially in recruitment, payroll, and labor contracts, which directly or indirectly affect the rights of migrant fishermen. On the other hand, although the C188 Work in Fishing Convention has stregthend the protection of the fishermen’s human rights, it still stays ambiguous in terms of private agency management. That is also why so many disputes have been caused in recent years.This study conducts a comparative analysis of the agency management systems in the primary source countries of Taiwan’s distant water fishing migrant fishermen (that is, Indonesia, the Philippines, and Vietnam), as well as interviews with distant water fishing stakeholders to provide insights on the improvement of agency management and migrant fishermen’s rights in Taiwan. The findings imply that the positive interaction, mutual trust, and understanding of laws and regulations between fishermen’s exporting and importing countries lead to future cross-national collaboration. This study suggests that the Taiwanese government should follow the spirit of the C188 but not be restricted to the Convention texts to amend or formulate regulations and policies of agencies for fully protecting the rights of migrant fishermen.

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)